Conductivity studies on chitosan/PEO blends with LiTFSI salt - Hassan, M.F. (2005)
Chitosan/PEO-LiTFSI films have been prepared by the solution cast technique. The highest conductivity at room temperature was 1.4 x 10(-6) Scm(-1) and the activation energy was 0.47 eV for chitosan/PEO blends containing 30 wt.% LiTFSI salts. The conductivity of the samples is dependent on the number of mobile ions.